An automated text summarization methodology - Jusoh, Shaidah; Masoud, Abdulsalam; Al Fawareh, Hejab M. (2009)
Most of the information is embedded in a long text documents.Having a summarizer that can produce a summary from the texts automatically is very desirable.This paper presents an introduction of an automated text summarization system by addressing the history of summarization and its existing application tools, and proposes a methodology for an automated text summarization.The proposed methodology utilized possibility and probability theory in the sentence extraction and sentence abstraction.The possibility and probability are also utilized in identifying relevant words and term occurrences techniques.